2011
DOI: 10.1007/s10875-011-9571-1
|View full text |Cite
|
Sign up to set email alerts
|

Altered Phenotype and Functionality of Circulating Immune Cells Characterize Adult Patients with Nonalcoholic Steatohepatitis

Abstract: Nonalcoholic steatohepatitis (NASH) is a chronic inflammatory liver disease associated with insulin resistance and its metabolic consequences. Leukocyte mobilization, intrahepatic activation, and an exacerbated production of reactive oxygen species (ROS) and cytokines contribute to the development of NASH. Though alterations in peripheral blood (PB) T cell proportions and functionality remain unidentified, they might play a main role in NASH progression. We have compared the phenotype and Th1/Th2 commitment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
95
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(112 citation statements)
references
References 42 publications
11
95
0
Order By: Relevance
“…+ and CD8 + cells in the peripheral blood; no change was observed for IL-4 + CD4 + cells (21). Further data on the impact of intrahepatic Th1 and Th2 effector T cells in NASH are derived from mouse experiments in various models of NASH.…”
Section: Discussionmentioning
confidence: 99%
“…+ and CD8 + cells in the peripheral blood; no change was observed for IL-4 + CD4 + cells (21). Further data on the impact of intrahepatic Th1 and Th2 effector T cells in NASH are derived from mouse experiments in various models of NASH.…”
Section: Discussionmentioning
confidence: 99%
“…28 Additionally, dietary reversion suppressed uncoupling protein 2 expression and increased hepatic ATP levels, conditions that might favor apoptosis rather than reactive oxygen speciesmediated hepatocyte necrosis. 29 Neutrophil dysfunction was also associated with liver fibrosis and cirrhosis in NASH. Indeed, human neutrophil peptides have the ability to enhance hepatic fibrosis in fatty liver diseases by inducing hepatic stellate cell proliferation.…”
Section: Neutrophils and Non-alcoholic Fatty Liver Diseasementioning
confidence: 99%
“…In addition, cytokines are not only being produced by local sources but also by peripheral blood cells. The presence of an altered phenotype and functionality of circulating immune cells has been speculated to be a distinctive characteristic in NASH patients [76,77] . Innate immune cells have the ability to secrete cyto-kines and to promote influx of inflammatory cells.…”
Section: Immune Cells and Cytokinesmentioning
confidence: 99%
“…Innate immune cells have the ability to secrete cyto-kines and to promote influx of inflammatory cells. To date, emerging strong evidences suggested that cytokines such as TNF-α and IL-1 are sensitising factors acting upon leukocyte infiltration of the liver [76,78] . These cytokines and chemokines effects contributed to intracellular oxidative stress and mitochondrial dysfunction, which amplified hepatocytes damage.…”
Section: Immune Cells and Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation